Food Safety And Hygiene Standards In The Hospitality Industry (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: With rapid technological changes in the field of food safety, we are moving  away from traditional means of cooking and preservation to highly advanced mechanisms and  procedures like Sous Vide, High Temperature Short Timing, Irradiation Techniques etc. These  changes also bring growth of hospitality industries such as international and national tourism,  restaurants, fast-food outlets and catering businesses. Objective: To gain knowledge about the  preferences of the customers about food and its safety and secondly to examine the current status  of Food and Hygiene standards in popular Quick Service Restaurants (QSRs). Methodology:  The whole research has been conducted by surveying the opinions of 50 customers regarding  their food habits, preferences, awareness about food safety laws. Fast food from popular fast  food QSRs were tested for contamination. Results: The research revealed that while 53% of  the respondents checked the hygiene of the outlet they ate in, yet 67% were unaware of the  food safety laws in the country. The food samples had negligible contamination except for  sample A that had 15 CFU/10ml. Conclusion: The research concluded that the consumers  need to be made aware and they also need to have some technical information related to the  said subject.
Keywords: Food Safety; Hygiene; HACCP; Fast Food; Contamination; FSSAI